Separação da camada limite turbulenta em Fluidos não-Newtonianos tipo lei de potência - Castellanos Gonzalez, Leonardo José (2018)
The present study presents an experimental and theoretical analysis of the behavior of turbulent flows of Newtonian and non-Newtonian power law fluids subjected to and adverse pressure gradient. Although the study of this phenomenon is a topic of research of great industrial importance, models and experimental data that describe it are limited, thus, the purpose of the work is to contribute to a better understanding of the mechanisms that govern the general behavior of this type of flows. Within this context, extensive measurement campaigns were conducted using, at the beginning, the particle image velocimetry technique to characterize and obtain data of the global behavior of the flows. Later, in order to understand the boundary layer structure, particularly in the region adjacent to the wall, measurements with laser Doppler anemometry were performed at several stations, located before and during separation. To perform the tests, a two-dimensional water tunnel was designed and built with a test section made of transparent acrylic. Three geometries were analyzed: the first, a backward facing step with an aspect ratio of 2: 1 and finally two smooth ramp with slopes of θ = 15◦ e 30◦ , respectively. For the non-Newtonian case, a sodium Carboxymethyl cellulose aqueous solution was used, which, after some rheometer tests, showed a totally shear thinning behavior. The implemented procedures contributed to obtaining new experimental data for the characterization of this phenomenon, introducing a new theory in the study of the separation analyzing, besides the shear stress at the wall, the influence of the turbulence and the Reynolds number in the position of the point of separation and re-attachment of the turbulent boundary layer.